The Effect of Brand Personality on Electronic Word-of-Mouth: Mediation of Brand Love and Moderated Mediation of Brand Experience Sharing - Liu, Manlin; Yan, Jinzhe (Frontiers in Psychology, 2022)
The knowledge payment industry will rapidly attract many enterprises that provide knowledge services. This study investigates the interrelationship between brand personality, brand love, and electronic word-of-mouth in the context of knowledge payment. Moreover, this study explored the brand experience sharing boundary condition by adopting a survey. Firstly, the main research results show that brand personality has a significant positive impact on brand love. Secondly, brand love also has a significant positive influence on electronic word-of-mouth. Thirdly, brand experience sharing plays a positive role in regulating brand love and electronic word-of-mouth. This research promotes e-marketing by focusing on brand personality, brand love, e-word of mouth, and other perspectives to improve business operations, user experience, and engagement, providing dedicated products or services to the customer base for profit. As an emerging market, knowledge payment will attract the participation of many knowledge service enterprises.